\[\large \frac{a^2+b^2+c^2}{ab+bc+ca}+\frac{1}{3}\geq\frac{8}{9}\bigg(\frac{a}{b+c}+\frac{b}{a+c}+\frac{c}{a+b}\bigg)\] Let \(a,b,c>0\), prove the above inequality.

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestHere's the solution. First, without losing generality, we can assume that \(ab+bc+ac=3\), the problem'll become \[a^2+b^2+c^2+1\geq\frac{8}{3}\bigg(\frac{a}{b+c}+\frac{b}{c+a}+\frac{c}{a+b}\bigg)\] Now we'll do some manipulation on the variables in \(LHS\) \[\frac{a}{b+c}+\frac{b}{c+a}+\frac{c}{a+b}=\frac{a(a+b)(a+c)+b(b+a)(b+c)+c(c+a)(c+b)}{(a+b)(b+c)(c+a)}\] \[=\frac{a^3+b^3+c^3+(a+b+c)(ab+bc+ca)}{(a+b+c)(ab+bc+ca)-abc}=\frac{(a+b+c)(a^2+b^2+c^2-ab-bc-ca+ab+bc+ca)+3abc}{3(a+b+c)-abc}\] \[=\frac{(a+b+c)(a^2+b^2+c^2)+3abc}{3(a+b+c)-abc}\] So now the inequality is \[a^2+b^2+c^2+1\geq\frac{8[(a+b+c)(a^2+b^2+c^2)+3abc]}{9(a+b+c)-3abc}\] \[\Rightarrow [9(a+b+c)-3abc](a^2+b^2+c^2+1)\geq 8(a+b+c)(a^2+b^2+c^2)+24abc\] \[\Leftrightarrow 9(a+b+c)(a^2+b^2+c^2)+9(a+b+c)-3abc(a^2+b^2+c^2)-3abc\geq 8(a+b+c)(a^2+b^2+c^2)+24abc\] \[\Leftrightarrow (a+b+c)(a^2+b^2+c^2+9)\geq 3abc(a^2+b^2+c^2+9)\] \[\Rightarrow a+b+c\geq 3abc\] The last inequality can be proven easily by these following inequalities: \((a+b+c)^2\geq 3(ab+bc+ca)\) and \(abc\leq\sqrt{\big(\frac{ab+bc+ca}{3}\big)^3}\). The equality holds when \(a=b=c\)

Log in to reply